"clickable" Organic Electrochemical Transistors - Fenoy, Gonzalo Eduardo (2022)
Interfacing the surface of an organic semiconductor with biological elements is a central quest when it comes to the development of efficient organic bioelectronic devices. Here, we present the first example of "clickable"organic electrochemical transistors (OECTs). The synthesis and characterization of an azide-derivatized EDOT monomer (azidomethyl-EDOT, EDOT-N3) are reported, as well as its deposition on Au-interdigitated electrodes through electropolymerization to yield PEDOT-N3-OECTs. The electropolymerization protocol allows for a straightforward and reliable tuning of the characteristics of the OECTs, yielding transistors with lower threshold voltages than PEDOT-based state-of-the-art devices and maximum transconductance voltage values close to 0 V, a key feature for the development of efficient organic bioelectronic devices. Subsequently, the azide moieties are employed to click alkyne-bearing molecules such as redox probes and biorecognition elements. The clicking of an alkyne-modified PEG4-biotin allows for the use of the avidin-biotin interactions to efficiently generate bioconstructs with proteins and enzymes. In addition, a dibenzocyclooctyne-modified thrombin-specific HD22 aptamer is clicked on the PEDOT-N3-OECTs, showing the application of the devices toward the development of organic transistors-based biosensors. Finally, the clicked OECTs preserve their electronic features after the different clicking procedures, demonstrating the stability and robustness of the fabricated transistors.